A study on learners’ readiness and perceptions of the implementation of blended learning in UiTM Kedah / Zetty Harisha Harun, Robekhah Harun and Laura Christ Dass - Harun, Zetty Harisha; Harun, Robekhah; Christ Dass, Laura (Akademi Pengajian Bahasa, 2019)
The increase in student enrolment and the need to cater to students of diverse backgrounds have led to the adoption of blended learning in many higher learning institutions. Blended learning, which allows both face to face interaction and on-line delivery, has been adopted into many curricula. One such institution is University Technology MARA which is slowly introducing features of blended learning in its course syllabus beginning with practice to online assessments. However, to ensure successful implementation of blended learning as part of the curricula, there are several aspects for consideration such as learner and teacher readiness for blended learning. This paper examines issues regarding the use of blended learning as a delivery method at UiTM Kedah . The discussion in this paper focuses on learner’ readiness and perceptions of the blended learning environment. The data collected for this study are responses from learners to a questionnaire survey. The research findings form the basis for recommendations for the development of learning and teaching practices using blended learning approaches to enhance learners’ learning experiences.